Programmed learning aid for production and operations management - Buffa, Elwood Spencer (Illinois : Learning Systems Company, 1981)
This book is to provide the readers with a quick, efficient, and effective means of grasping the essential subject matter on production and operations management.
.
Includes index
usc 21/06/2017
Loans
Keywords: Production management; Industrial management